2016
DOI: 10.7324/japs.2016.60413
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative growth, chemical composition, and flavonoids content of Azadirachta indica plants as affected by application of yeast natural extract

Abstract: This experiment was carried out during 2013 and 2104 seasons on Azadirachta indica plants at National Research Centre greenhouse, Egypt. Experiment studied the effect of foliar spraying plants with dry yeast (Saccharomyces cerevisiae) extract at various concentrations (0, 5, 10, 15 and 20%) on growth, pigments, NPK (%), total soluble sugars, indoles, phenols and flavonoids leaves contents. Results showed that spraying neem plants with yeast extract at 15% significantly increased growth parameters (plants heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
4
8
0
Order By: Relevance
“…While there was no significant difference between spraying the plants with active dry yeast or Allium sativum extract in the two cuts in both seasons. This was supports the results of Ahmed (2009) on Melissa officinalis, Nassar (2015) on basil, Matter and El Sayed (2015) on caraway and Taha et al (2016) on Azadirachta indica plants.…”
Section: A-growth Characters: Plant Height and Number Of Branches Persupporting
confidence: 87%
See 1 more Smart Citation
“…While there was no significant difference between spraying the plants with active dry yeast or Allium sativum extract in the two cuts in both seasons. This was supports the results of Ahmed (2009) on Melissa officinalis, Nassar (2015) on basil, Matter and El Sayed (2015) on caraway and Taha et al (2016) on Azadirachta indica plants.…”
Section: A-growth Characters: Plant Height and Number Of Branches Persupporting
confidence: 87%
“…Moreover, the increments in NP as a result of active dry yeast and Allium sativum extract application may be attributed to their favorable effect on marjoram plants growth (Tables 1 and 2) as mentioned earlier (Ahmed, 2009). Some reviewers conformed the present findings using other medicinal and aromatic plants; for instance, Nassar (2015) on basil, Matter and El Sayed (2015).on Caraway and Taha et al (2016) on Azadirachta indica plants.…”
Section: A-growth Characters: Plant Height and Number Of Branches Persupporting
confidence: 83%
“…For the interaction effect of chicken manure (ChM) % with dry yeast spraying concentrations data clear that 100 % from the recommended N rate as chicken manure (ChM)with spraying lavender plants with 200 ppm dry yeast resulted in significant enhancement on total nitrogen, phosphorus and potassium percentage (%) of the two seasons. These results are similar with those found by Taha et al, (2016) studied the effect of foliar spraying plants with dry yeast (Saccharomyces cerevisiae) extract at various Concentrations (0,5, 10, 15 and 20%) on nitrogen content. Results suggested that nitrogen content was enhanced and recorded the maximum value in plants treated with dry yeast extract at 10%.…”
Section: Oil Percentage (%) and Oil Yield/ Fed (L)supporting
confidence: 91%
“…The obtained results were similar as found by Mohamed et al, (2017) on Ocimum basilicum, L. var Genoves plant they reported that fresh and dry weights increased especially the interaction treatment between chicken manure20 m 3 / fed. with yeast extract 100 M/ L in the two cuts and in the Taha et al, (2016) studied the effect of foliar spraying neem plants with dry yeast (Saccharomyces cerevisiae) extract at different concentrations (0, 5, 10, 15 and 20%) on growth. Results showed that growth parameters increased significantly by spraying plants with yeast extract at 15%.…”
Section: Herb Fresh Weight (G)/ Plantmentioning
confidence: 99%
“…Yeast extract is a very interesting natural plant inducer due to its role in producing some growth regulators, as well as its ability to act as a biostimulant of plant growth or the biosynthesis of plant pigments and some other bioactive compounds [3,4]. For example, in a study conducted by Zlotek et al [5], yeast extract (0.1% and 1%) elicitation increased the level of phenolic compounds and chlorophylls in lettuce leaves.…”
Section: Introductionmentioning
confidence: 99%